CLASS PARTICIPATION AND PROFICIENCY IN ENGLISH SUBJECT: BASIS FOR ENGLISH CURRICULUM DEVELOPMENT - Irene A. Sanchez; Cris S. Saranza (European Journal of Humanities and Educational Advancements, 2023)
This study assessed the class participation and proficiency in English of 501 grade 7 students and 17 English teachers of Surigao del Norte, Philippines. Data were gathered from the survey questionnaire and were analyzed using mean and ordinal rank, t-test and Pearson-r, and Analysis of Variance for dependent samples. Results showed that grade 7 students are moderately participative in class undertakings by orally answering questions, performing group and board works, and role play, and are proficient in English in terms of reading, speaking, writing, and listening. It also showed a significant relationship between class participation and reading proficiency; however, no significant difference exists between the extent of class participation and the reading proficiency of the respondents